The importance of mammography in the prevention of breast cancer in women in Norway - Renata Pałac; Aneta Mielnik; Elżbieta Cipora (Journal of Education, Health and Sport)
Introduction. Breast cancer in women in the world is the dominant cancer and the main cause of death in this population.In the last decade, the number of new cases of this cancer has increased significantly, especially among women over 50 years of age. In Norway, however, positive epidemiological trends can be observed in the form of high relative five-year survival rates and a decrease in mortality due to breast cancer.